2021
DOI: 10.1177/17454999211039298
|View full text |Cite
|
Sign up to set email alerts
|

World class universities and international student mobility: Repositioning strategies in the Asian Tigers

Abstract: A major cluster of economic engines that have changed Asian higher education, Hong Kong, Singapore, South Korea, and Taiwan have all developed high-income societies as well as world-class universities which linked local “knowledge economies” to global science and created hubs for international collaborations and mobility. However, there has been limited analysis of interdependencies between the rise of world-class universities and changes in the flows of international talent. This paper elaborates on the conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 102 publications
0
14
0
Order By: Relevance
“…As a new international trend of educational concepts and models, E&I education has attracted widespread attention from all over the world, and has gradually become an important part of modern education, especially higher education [15][16][17]. In contrast to conventional education model and the E&I education system of other types of universities, the uniqueness of E&I education for colleges in the STS industry mainly manifests in the following dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…As a new international trend of educational concepts and models, E&I education has attracted widespread attention from all over the world, and has gradually become an important part of modern education, especially higher education [15][16][17]. In contrast to conventional education model and the E&I education system of other types of universities, the uniqueness of E&I education for colleges in the STS industry mainly manifests in the following dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…According to another interviewee, the cost of studying in the UK for a year is about 400,000–500,000 RMB (about 59,200–74,000 dollars). In addition, Singapore universities offer generous scholarships that enhance their attractiveness to international students ( Oleksiyenko, A. V., et al, 2021 ). NUS, for example, offers a variety of scholarships and grant allowances such that all international students have the option to apply for the scholarship program.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, most Chinese students studied abroad in Western countries. However, existing research has shown that mainland Chinese students are more likely to recognize the educational quality and international reputation of Hong Kong universities and see Hong Kong as a stepping stone for further internationalization ( Li and Bray, 2007 ; Oleksiyenko, A. V., et al, 2021 ). “Actually, HKU is very good, and many of the teachers in my undergraduate school have studied in Hong Kong before.” (The University of Hong Kong, Master’s Program, Social Sciences, No.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different scholars have different interpretations and classifications of "push" and "pull". The most common "pull" factors are from the receiving country, such as the education quality and reputation [6]; institutions or state funding [7];university ranking [8]; security level [9]; and political and economic reasons of other countries. The factors of "push" include the poor quality of education in the exporting countries [10]; popular "returnees" for employers; some specific disciplines [11], and other political and economic reasons.…”
Section: Literature Reviewmentioning
confidence: 99%